Impacts of agricultural expansion on floodplain water and sediment budgets in the Mekong River - Park, Edward; Loc Ho, Huu; Van Binh, Doan; Kantoush, Sameh; Poh, Danielle; Alcantara, Enner [UNESP]; Try, Sophal; Lin, Yunung Nina (Elsevier, 2022)
In this paper, we address the impact of agricultural expansion on hydrological patterns of water and sediment budget in one of the largest floodplains along the Cambodian Mekong since the 1980s, using field (water level, discharge, sediment, rainfall, and groundwater level) and remote sensing (land use, surface suspended sediment) data, and numerical simulations. Specifically, while both the surface suspended sediment concentration and water level in the Mekong River around Kampong Cham and Neak Luong decreased, the floodplain seasonal water storage increased. In addition, the rate of sediment input from the river to the floodplain was almost constant throughout the studied period. The investigation of the floodplain's annual sediment budget, however, reveals a significant drop during the analyzed period, mainly due to the decreased sediment trapping rate (66% in the 1980s to 46% in the 2010s). Currently, a good amount of sediment bypass the floodplain and return back to the river. The observed hydrological patterns in the floodplain could have been triggered by the agricultural expansion that has increased surface erodibility (due to removals of primary vegetation) and lowered the land surface elevation (due to groundwater extraction). Despite the well-known impacts of the hydropower dams on the Mekong Delta hydrological conditions, particularly the reduction of sediment reaching the delta due to sediment trapping by dam reservoirs, our observations point to new and more localized driving factors of sediment deficit in floodplain: agricultural expansion. Finally, we used 2D hydrodynamic simulation (Telemac-2D) to visualize the processes of water routing and sedimentation in the floodplain accounting for land cover change since the 1980s. The floodplain hydrology reported in this paper is an unexplored environmental consequence of agricultural expansion in the lower Mekong. Geomorphologically, this study presents a peculiar case of floodplain showing how agricultural expansion can diminish the role of a floodplain as a sediment sink through decreasing the trapping rate.
Keywords: Cambodia; Floodplain; Human impacts; Land use land cover change; Mekong; Sedimentation